Distance Parenting and its Effects to the Children of OFW’s in Balayan, Batangas, Philippines (American Journal of Human Psychology, 2025)
A child may be well provided for in a material sense, but utterly deprived of emotional nurturance; This places the child in a state of psychological conflict, even turmoil. He may be grateful on the one hand , but angry and hurt on the other (due to emotional deprivation).This paved the way for the researchers to conduct this study. The following are the Objectives of the Study:1.What is the profile of the OFW parent? the results showed that there are more OFW mothers than Fathers with 85 respondents or 61.15% percent and 54 Fathers or 38.84%. 2.Who takes care of the child? Father got the highest number of respondents with 43 or 31%, next is grandmother which got 34 or 25% and the lowest is grandfather which got 1 or 1% 3. What is/are the age/s of children? As to the age of the OFW children. The highest is age 16-20 which got 54 or 39%,And the lowest is ages 1-5 which got 10 or 7%. 4.What is the length of period the Parent is working abroad? majority of the OFW parents worked for 6-10 years which has 79 or 57%, followed by 1-5 years which got 30 or 22% and the lowest is 1616-20 years which got 6 or 4%. 5.What are the effects of distance parenting to the children left behind by OFWs.? well behaved got the highest with 67 or 48.25%,and the lowest is not behaved which got 4 or 2.9%. Across the country’s 17 regions, CALABARZON contributed the largest number of OFWs which was estimated at 15.9 percent or 159 in every 1,000 OFWs in 2021.